Exploring Resilience As A Mediator In The Relationship Between Religiosity And Social Support On Psychological Well-Being Of Worker - Soplantila, Frieska; Sandra, Lidia (Action Research Literate, 2024)
This study investigates the mediating role of resilience in the relationship between religiosity, social support, and psychological well-being among university employees. Employing a quantitative approach, the research examines how these variables interact to influence the mental health of this demographic. The results, based on a sample of 345 university employees, indicate that while religiosity does not have a direct, significant impact on psychological well-being (p > 0.05), it indirectly affects well-being through resilience, which functions as a full mediator. This finding suggests the transformative role of resilience in channeling religious beliefs towards enhanced mental health. In contrast, social support shows a direct, albeit small, significant impact on psychological well-being. The study highlights the nuanced interplay between personal belief systems, social support, and psychological well being. It proposes that enhancing resilience and strengthening social support systems could be crucial for improving the psychological well being of university employees.